PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAI BERBASIS BAAMBOOZLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD INPRES 12/79 ARASOE - Firdaus; Asriadi; Pratiwi, Tasyah (MACCA : Science-Edu Journal, 2025)
This research is classroom action research which aims to find out how the application of the TAI type cooperative learning model based on Baamboozle can improve the Mathematics learning outcomes of fourth grade students at SD Inpres 12/79 Arasoe, Cina District, Bone Regency. The approach used in this research is descriptive qualitative. The subjects in this research were all 17 class IV students and the class IV homeroom teacher. Data collection techniques use observation and tests. The data analysis techniques in this research are reducing data, describing data and drawing conclusions. The research results showed that teacher activity in processing learning experienced an optimal increase from cycle I to cycle II as seen from teacher activity in carrying out good learning activities in accordance with the steps of the Baamboozle-based TAI type cooperative learning model. Student activity in participating in learning activities has increased from cycle I to cycle II as seen from observations during learning activities using observation sheets. As for student learning outcomes in cycle I, there were 12 out of 17 students who got a complete score with an average score of 70.88 with a percentage of student learning completeness reaching 70.58% (enough), and experiencing an increase in cycle II there were 14 out of 17 students who got a complete score with an average score of 78.52 with a percentage of student learning completeness reaching 82.35% (good). It can be concluded that the TAI type cooperative learning model based on Baamboozle can improve students' Mathematics learning outcomes